The Consolidation of EU Governance: The European Semester and the Evaluation of European Integration Deepening - Nicolae Toderas; Ana-Maria Stavaru (CES Working Papers, 2016)
Once it was introduced as an instrument for deepening European integration, the legitimacy, opportunity and utility of European Semester were repeatedly questioned from the perspective of its contribution to the institutionalization of European governance. Also, there is a strong and direct link between the further deepening of the European Union's political and economic integration on the one hand, and the development of a culture of evaluating policies and programs on the other. Taking these aspects into account, the following questions arise: does the European Commission have, in its position as manager of the European Semester, a real capacity of evaluating all aspects regarding the deepening of European integration? Can the European Semester be a means for diffusing evaluation practice at the level of Member States? This is why, in this paper, we propose to give answers to these questions.
Keywords: D04; D78; F42; O20; 330; European Semester; governance; evaluation